2017
DOI: 10.1038/s41467-017-00473-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic correlations reveal the shared genetic architecture of transcription in human peripheral blood

Abstract: Transcript co-expression is regulated by a combination of shared genetic and environmental factors. Here, we estimate the proportion of co-expression that is due to shared genetic variance. To do so, we estimated the genetic correlations between each pairwise combination of 2469 transcripts that are highly heritable and expressed in whole blood in 1748 unrelated individuals of European ancestry. We identify 556 pairs with a significant genetic correlation of which 77% are located on different chromosomes, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…The weak correlations between blood-based traits and growth traits limit the potential for blood-based traits to be used as indicators of performance under varying environments. Strong genetic correlations between blood-based traits indicate the existence of an important overlap in genetic control and can be considered as evidence of pleiotropic effects playing a role in regulating multiple blood-based traits as found previously by Lukowski et al (2017).…”
Section: Discussion Most Blood-based Traits and Growth Traits Are Weasupporting
confidence: 56%
“…The weak correlations between blood-based traits and growth traits limit the potential for blood-based traits to be used as indicators of performance under varying environments. Strong genetic correlations between blood-based traits indicate the existence of an important overlap in genetic control and can be considered as evidence of pleiotropic effects playing a role in regulating multiple blood-based traits as found previously by Lukowski et al (2017).…”
Section: Discussion Most Blood-based Traits and Growth Traits Are Weasupporting
confidence: 56%
“…First, Nath et al identified highly correlated groups of mRNA transcripts and metabolites (termed 'modules'), and performed genome-wide scans to associate specific SNPs with variation in each module 19 . In a related analysis, Lukowski et al demonstrated that mRNA transcripts with evidence for genetic correlations were more likely to be regulated by the same expression quantitative trait loci (eQTL) 36 . Finally, van der Wijst recently leveraged single-cell mRNA-seq data from 45 individuals to build personalized co-expression networks, and used these data to identify genetic variants that predicted interindividual variation in correlation structure 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Lukowski et al (2017) tested for genetic covariance between gene pairs, and identified 15,000 gene pairs (0.5% of all gene pairs) with significantly nonzero genetic covariance at 5% FDR [47]. Since effect on gene j acts through the regulatory network, effectively like a peripheral variant, although the GWAS signal itself would be found in cis to k. This effect would slightly increase the measured contribution of core gene variants to heritability, although it seems likely to be a modest effect unless core genes make up a large fraction of all genes.…”
Section: Core Gene Effects On Heritabilitymentioning
confidence: 98%